The Typology of Physical Qualities - Rakhilina, E. V. (Ekaterina V.); Reznikova, T. I. (Tatʹi︠a︡na Isidorovna); Ryzhova, Daria (Typological studies in language., 2022)
This volume presents a lexico-typological study of several domains of physical qualities: 'sharp'/'blunt', 'wet', 'empty'/'full', 'old', as well as dimensions and surface texture.